A Classificatory Note on the Determinateness of Equilibrium - Kaldor, Nicholas (Review of Economic Studies, 1934)
A Classificatory Note on the Determinateness of Equilibrium Nicholas Kaldor Nicholas Kaldor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 122–136, https://doi.org/10.2307/2967618 Published: 01 February 1934